2022
DOI: 10.3390/endocrines3020016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma or Urine Neutrophil Gelatinase-Associated Lipocalin (NGAL): Which Is Better at Detecting Chronic Kidney Damage in Type 2 Diabetes?

Abstract: Background and study aims—Albuminuria, defined as an enhanced urine albumin/creatinine ratio (ACR) on a spot sample, is a validated biomarker of glomerular damage. However, it cannot always detect early renal failures in patients with type 2 diabetes (T2D), thus prompting the search for more sensitive and specific parameters. Herein, we investigated the differential role of plasma and urine neutrophil-gelatinase-associated lipocalin (NGALp,—NGALu) for the detection of diabetic kidney disease (DKD). Methods—Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…A further concern is the considerable diversity in algorithms employed for normalizing miRNAs in the context of disease association studies, encompassing methods such as spike-in normalization, small nucleolar RNA normalization and mean-centric normalization. In light of this, the Global Ct mean normalization has recently undergone validation as the most effective normalization method in highthroughput miRNA profiling studies where the process of miRNA biomarker identification is initiated [31]. The use of diverse normalization techniques in high-throughput miRNA profiling studies may explain the lack of prior reports indicating an association between T2D and the increased expression of circulating hsa-miR-1225-3p [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further concern is the considerable diversity in algorithms employed for normalizing miRNAs in the context of disease association studies, encompassing methods such as spike-in normalization, small nucleolar RNA normalization and mean-centric normalization. In light of this, the Global Ct mean normalization has recently undergone validation as the most effective normalization method in highthroughput miRNA profiling studies where the process of miRNA biomarker identification is initiated [31]. The use of diverse normalization techniques in high-throughput miRNA profiling studies may explain the lack of prior reports indicating an association between T2D and the increased expression of circulating hsa-miR-1225-3p [62].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation (C-Reactive Protein (CRP) > 6 mg/L; Erythrocyte Sedimentation rate (ESR) > 30 mm/h), obesity (BMI > 30 kg/m 2 ), poor glycemic control (glycated hemoglobin, HbA1c > 8%, 64 mmol/mol), smoking, alcohol and drug use, including antidiabetic pharmacological medications with possible impact on miRNAs (i.e., metformin [29]), as well as intercurrent illnesses and moderate-to-severe hypertriglyceridemia (triglycerides > 175 mg/dL, 2.0 mmol/L) were assumed as exclusion criteria. Additionally, in consideration of the possible alterations in miRNA expression throughout the various stages of chronic kidney disease [18,30], to mitigate any potential bias in the detection of circulating miRNAs that are specifically linked to the progression from prediabetes to T2D, individuals with indications of renal impairment (such as an estimated glomerular filtration rate < 60 mL/min/1.73 m 2 or the presence of microalbuminuria), regardless of whether it was related to diabetic nephropathy [31], were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to hyperglycemia and insulin resistance, hypertension, dyslipidemia, smoking, drinking history, and other factors will lead to progressive renal dysfunction and microcirculatory disorder, which will aggravate the occurrence and development of diabetic nephropathy [ 16 ]. Cui et al found that the circulating EDA level of NAFLD patients was significantly higher than that of healthy subjects [ 11 ], which was further confirmed by Bayliss et al [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in urinary lipocalin-2 amounts was noticed in diabetic patients with clinical signs of renal diseases. In the cohort of diabetic patients, urinary lipocalin-2 levels positively correlated with serum creatinine, cystatin C, hemoglobin A1c (HbA1c) and albuminuria [ 111 ].…”
Section: Adipokines In Urine and Fecesmentioning
confidence: 99%